Women’s right to lead her marriage contract (‘aqd) under Islamic law: an appraisal of the differences of opinion among the majority (Jumhur) and the Hanafi school of law - Mohd, Azizah; Ibrahim, Badruddin (Serials Publications, 2014)
Women in Islam are among special creatures created by Allah al-mighty as men’s partners in family life. Due to their certain physical and spiritual weaknesses as compared to men, they are ought to be protected from many occasions that may cause harm and hardship on them. In principle, Islam regards men as women’s protector and supporter and this is clearly understood from the verse of the Quran in Surah al-Nisa, 4: 34 which states among others that men are protectors and supporters of women because Allah has given them more strength than the women. Apart from the protection, they are guaranteed of many rights and privileges which include rights to fundamental liberties and rights in family relationship. This paper seeks to examine the right of women in the very beginning of a family relationship i.e. their right to lead her own marriage contract under Islamic law. The focus will be on the differences of opinion among the view of the majority (Jumhur) and the Hanafi school law. This paper is undertaken based on several books written by contemporary Muslim Scholars as to make it practical to the current practice of the people.